Random Attractors for Stochastic Three-Component Reversible Gray-Scott System on Infinite Lattices - Anhui Gu; Zhaojuan Wang; Shengfan Zhou (Discrete Dynamics in Nature and Society)
We prove the existence of a compact random attractor for the random dynamical system generated by stochastic three-component reversible Gray-Scott system with a multiplicative white noise on infinite lattices.